VC's Award for Sarimah Ahmad - Mahat, Mohd Shah (UiTM Sarawak, 2004)
Sarimah Ahmad made the Faculty of Accountancy and UiTMCS staff proud when she successfully completed her DIA with flying colours, winning the Vice Chancellor's Award in the March 04 examination. During the pre-graduation dinner on Feb 04, Sarimah received her Best Student award, from the CEO of Parabena Group, Dato Raziah Mahmud. Sarawak's State Legislative Assembly Speaker, Dato Sri Haji Mohamad Asfia Awang Nassar who spoke before 400 guests at the function gave some useful tips for the young graduates. He said that "Knowledge is more valuable than property. With knowledge you can exercise power. Knowledge is superior to property because it is knowledge that looks after the property".